Does Islamic Finance Boost the Economic Growth? Evidence from Indonesia - Azwar; Haliding, Safri; Majid, Jamaluddin (AL-MUZARA'AH, 2024)
Although the growth of the sharia financial industry continues to increase in Indonesia, there is a need to understand the impact of the development of Islamic finance, including sharia banking, sharia bonds (sukuk), sharia shares, and sharia mutual funds, on Indonesia's economic growth. Previous research has highlighted a positive relationship between financial sector development and economic growth in general, but there has been no specific research examining the impact of Islamic financial instruments specifically in the Indonesian economic context. This study aims to analyze the effect of Islamic finance development consisting of Islamic banking, Islamic bonds (sukuk), Islamic stocks, and Islamic mutual funds, both partially and simultaneously, on Indonesian economic growth during the period of 2003-2022. This study uses a quantitative approach with the Ordinary Least Square (OLS) technique. The results of the study show that the Islamic banking and Islamic bonds (sukuk) have a positive and significant influence on the economic growth in Indonesia, the Islamic stocks also was found to has a positive effect on economic growth but not significant, while the Islamic mutual funds was found to has a negative and not significant effect on the economic growth. It implies that government may continuously support to sukuk for sustainable economic growth and the policy for the development of Islamic finance should be improved to increase the income of government particularly for Islamic stock and Islamic mutual fund.